Image-guided chemoport insertion by interventional radiologists: A single-center experience on periprocedural complications - Yaacob, Yazmin; Nguyen, DangV; Md Ralib @ Md Raghib, Ahmad Razali; Muda, Sobri; Zakaria, Rozman; Mohamed, Zahiah (PubMed Index, 2013)
Purpose: To report our early experience in image-guided chemoport insertions by interventional radiologists. Materials and Methods: This was a cross-sectional study conducted in a tertiary center with 161 chemoport insertions done from June 2008 to June 2010. The chemoports were inserted either at the angiography suite or at the mobile operation theater unit. Ninety percent of the chemoports had right internal jugular vein (IJV) as the entry site. Other entry sites included the left IJV, subclavian veins and the inferior vena cava. Immediate and early complications were recorded. All insertions were performed under image guidance with the aid of ultrasound and fluoroscopy. Results: The technical success rate was 99.4%. In terms of immediate complications, there were only two cases of arterial puncture that resolved with local compression. No pneumothorax or air embolism was documented. Twenty-six early complications were recorded. The most common early complication was catheter blockage (12/161; 7.4%), followed by catheter-related infection (9/161; 5.6%). Other complications were catheter malposition, venous thrombosis and catheter dislodgement or leak. A total of 11 (6.8%) chemoports had to be removed within 30 days; most of them were due to infections that failed to respond to systemic antibiotic therapy. In terms of place of procedure, there were no significant differences in complication rates between the angiography suite and the mobile operation theater unit. Conclusion: Image-guided chemoport insertion by interventional radiologist gives low periprocedural complication rates. Using right IJV as the entry site, the image guidance gives good success rate with least complication.